Implementasi Pendidikan Karakter di SMA Negeri 1 Kota Metro - Purwaningsih Purwaningsih (Jurnal Dewantara, 2018)
Character education is the basic value needed by every human being. For that, a good or bad environment can affect the character itself. Due to the data used in this study is qualitative data. Based on the results of research are: Implementation of character education in SMA Negeri 1 Metro has been run well; The school also has implemented character education through exemplary, such as teaching students to be honest, teaching students to discipline, using clothes politely then the teacher must be able to do it first before teach to students; In the implementation of character education in SMA Negeri 1 Metro influenced by internal factors include customs or customs, will of willingness and conscience as well as external factors including education and the environment. It is influenced by the custom or habit, the will and the conscience of the students themselves, but after the school made efforts to improve both in terms of education and school environment to shape the character of students.